Structural Modeling of Financial Literacy for Women of MSME Pacitan and Tangerang - Setyawan, Ignatius Roni; Ramli, Ishak; Listyarti, Indra (Budapest International Research and Critics University, 2021)
This study is aimed to determine the women's understanding of financial inclusion in making financial decisions in the family. Where previously this research will map the understanding of financial literacy that is owned by women in two regional locations, namely Pacitan Regency and Tangerang Regency. The form of empirical testing analysis which we have used is using Structural Equation Model (SEM) with nonlinear regression technique Partial Least Squares (PLS). Population affordable research, each district will be taken as many as 150 respondents in order to obtain a total sample of 300 respondents. The sampling technique used was snowball sampling, namely sampling based on recommendations from respondents from both regions. The results achieved are demographically mapped patterns of literacy and financial inclusion among women SMEs in Pacitan and Tangerang in terms of utilization of financial institutions, banking products & services, basic knowledge of finance and investment decisions. These two areas have different study results. In the next section, this research also succeeded in proving the existence of a structural modeling of literacy and inclusion of preferences for respondents Pacitan and Tangerang combined. The results of this study also confirm the effectiveness of structural modeling in the area of financial literacy research.